THE INFLUENCE OF CAPITAL STRUCTURE, COMPANY GROWTH, DIVIDEND POLICY, SALES GROWTH, AND INVESTMENT DECISIONS ON COMPANY VALUE IN PHARMACEUTICAL SUB-SECTOR COMPANIES LISTED ON THE IDX FOR THE 2018-2022 PERIOD - Norhasanah, Sitti; Dwi Astuti, Diana; Rachmawati, Lia (MBA : Journal of Management and Business Aplication, 2024)
This study aims to analyze the effect of capital structure, company growth, dividend policy, sales growth, and investment decisions on company value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX). This research was conducted for five consecutive years from 2018 to 2022 which included 8 company samples taken using a purposive sampling technique. The data analysis used is multiple regression analysis method. The results of this study indicate that partially capital structure, company growth, and investment decisions affect firm value. Sales growth and dividend policy have no effect on firm value. Simultaneously capital structure, company growth, dividend policy, sales growth, and investment decisions have a significant effect on firm value.